Chapter 2: Spatial agencing, privilege and new ways of working - Crevani, Lucia (Edward Elgar Publishing, 2023)
Privilege is ubiquitous but seldom discussed in organization studies. However, its analysis may enable us to explore those unrecognized advantages that systematically confer power on certain groups and individuals in specific contexts. In this chapter, we focus on the organizing agential properties of space and their power effects in terms of privilege. Building on Massey's work on space and place, we discuss privilege as an aspect of spatial agencing by illustrating how this is meshed into contemporary workplaces promoting new ways of working. This allows us to expand on spatial agencing by unpacking how, in the new workplace, the performative effects of assemblages can place some humans and nonhumans into privileged positions in terms of center-periphery, natural presence and otherness. Since such achievements are not only local but also related to other achievements in different times and places, we can also discuss how 'power-geometries' travel in time and space.